Effects on overall performance of feeding commercially grown pigs less or more than their lysine requirement in early and late finishing - R G Main; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 1154 gilts (PIC L337 × C22, initially 72.3 ± 1.7 lb) were used to determine effects on subsequent growth performance of feeding less than or at the estimated lysine requirement for optimal growth and feed efficiency in early finishing (70 to170 lb). From d 0 to 27 and d 27 to 55, pigs were fed a diet containing 2.75 and 2.25 g lysine/Mcal ME, respectively, which was less than their estimated requirement. Pigs fed at their estimated requirements were provided diets containing 3.30 and 2.75 g lysine/Mcal ME from d 0 to 27 and 27 to 55, respectively. Pigs within each early finishing treatment subsequently were fed less than, at, or more than (1.75, 2.25, 2.75 g lysine/Mcal ME, respectively) the estimated lysine requirement from 170 lb to slaughter at 255 lb. In early finishing (70 to 170 lb), pigs fed at the estimated lysine requirement had improved (P0.17) by late finishing dietary treatment. Overall IOMFC was not affected (P>0.62) by the lysine-to-calorie ratio (g lysine/Mcal ME) fed in early finishing (70 to 170 lb), and increased (linear, P0.89) d 0 to 104 IOMFC. Due to compensatory improvements in late finishing feed efficiency and feed cost per pound of gain, pigs fed diets less than biological requirements in early finishing, and subsequently fed at the estimated lysine requirement in late finishing, had lower (0.145 vs. 0.148 ± $0.001, P0.70) to that of pigs fed at the estimated dietary lysine requirement throughout finishing. Understanding the biologic and economic dynamics of over- and under-feeding lysine in early (70 to 170 lb) and late (170 lb to 255 lb) finishing provides guidance in formulating cost-effective feeding strategies. This study suggests that, as long as lysine requirements are being met in mid-late finishing (170 lb to slaughter), feeding slightly less than the lysine requirement for optimal performance in early finishing reduces feed costs without sacrificing overall IOMFC.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Compensatory Gain; Lysine; Pigs; Swine